A STUDY OF DUTCH SIEGE TACTICS AND FORTIFICATION DESIGNS IN ASIA DURING THE 17TH CENTURY - Lin , Yu-Ting (PEOPLE: International Journal of Social Sciences, 2024)
The purpose of this paper is to examine the relationship between the design concepts of Dutch siege fortifications and the VOC's siege practices in Asia in the 17th century. In terms of "the design concepts of Dutch siege fortifications," mainly based on the theoretical work OF BESIEGING TOWNS AND FORTRESSES (Vant Belegherin Der Steden en Sterckten), written by Simon Stevin (1548-1620), a Dutch military engineer. Stevin had served in the Dutch army as a military advisor to Prince Maurice of Nassau (1585-1625), co-planning a number of sieges. Moreover, he was designated to found the engineering school at Leiden University. Thus, Stevin's works reflect the tactics and design concepts of sieges in the 16th-17th centuries. Regarding "the VOC's siege practices in Asia," mainly derived from the establishment of the Dutch East India Company (Vereenigde Oost-Indische Compagnie, abbreviated as the VOC) in 1602. Its purposes were not only to gather wealth but also to attack the power of Spain and Portugal. The government empowered the VOC with the rights to recruit troops, purchase quality guns and cannons, and even represent the country to declare war or make peace with the flags of red, white, and blue. As a result, the globe-wide expansion of the VOC led to several sieges in Asia, as well as cross-cultural military exchanges between Europe and Asia.